Magneto-inducirane površinske strukture - Arh, Katja (Matrika, 2020)
This article introduces magneto-active elastomers and investigates the formulation of surface morphologies in the presence of an external magnetic field. The first part of the article describes coarse-grained modelling of magneto-active elastomers by means of molecular dynamics simulation. In the second part, optical methods for surface studies are presented, followed by measurements of surface roughness and time response of material. Finally, several samples are compared in order to determine optimal material composition for tunable surface roughness in presence of magnetic field.
Keywords: magnetoactive elastomers; magneto-aktivni elastomeri; površinske strukture; surface morphologies